Students' Environmental Awareness And The Citizenship Course: An Educational Policy Perspective - Tatang Sudrajat; Indrawati (Research Collaboration Community (Rescollacom), 2026)
Indonesia currently faces serious environmental damage, which significantly disrupts the sustainability of national development. Students play a crucial role in environmental conservation efforts by fostering awareness of environmental preservation. Government policies, such as Decree of the Director General of Higher Education (Kepdirjen Dikti) Number 84/E/KPT/2020 and several other state and government regulations, constitute public policies in the field of education that can contribute to environmental sustainability. This study aims to analyze the profile, context, and substance of state and government policies on the Civics course, which are relevant to environmental sustainability efforts from a public policy and education perspective. The research used normative juridical, qualitative, and literature study methods. The normative juridical method examined the substance of government regulations, while the qualitative method employed interviews with several lecturers and students as informants. The literature study examined all relevant sources and documents in various forms. The results of the study indicate that several state and government regulations constitute policies for the realization of environmental sustainability, including those related to higher education. The environmental theme integrated into the Citizenship course is very strategic as a preventive measure against environmental damage. Government officials at the Ministry of Environment, law enforcement officers, officials from the Ministry of Higher Education, Science, and Technology (Kemendiktisaintek), university leaders, lecturers teaching Citizenship courses, environmental figures and activists, students, and other educational stakeholders are policy actors. The threat of increasingly severe environmental damage and the need for students to understand it are policy issues. The Ministry of Environment, the Indonesian National Police, Kemendiktisaintek, universities, and various institutions outside the government are policy institutions. The public's expectation of students who are aware of and responsible for environmental sustainability is a policy issue. Several policy elements need to be refined.